2014
DOI: 10.1016/j.juro.2013.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Followup Imaging after Adult Pyeloplasty

Abstract: Purpose Although success rates are reported to be high, radiographic followup after pyeloplasty to correct ureteropelvic junction obstruction varies in intensity and modality. We characterized postoperative care after pyeloplasty to identify imaging trends. Materials and Methods Using the MarketScan® database we identified patients 17 to 65 years old treated with pyeloplasty from 2007 to 2010. Followup imaging was classified as functional (diuretic renogram or excretory urogram) and nonfunctional (ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
5
0
6
Order By: Relevance
“…8 Nuclear renography is also commonly used in the postoperative period for assessment of obstruction alleviation. 9 We have previously reported that RPV can be assessed easily and accurately using automated 3D reconstruction. 7 This method is yet to be used to evaluate function in obstructed renal units that subsequently underwent surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…8 Nuclear renography is also commonly used in the postoperative period for assessment of obstruction alleviation. 9 We have previously reported that RPV can be assessed easily and accurately using automated 3D reconstruction. 7 This method is yet to be used to evaluate function in obstructed renal units that subsequently underwent surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…Radionuclide renography is the most commonly used method, but it is difficult to evaluate the outcomes at different follow-up times using this technique [12,13]. A PCN catheter should remain inserted for about 4-12 weeks [1], but patients with PCN drainage are at increased risk of further renal function loss and infection [4,11].…”
Section: Discussionmentioning
confidence: 99%
“…9 Nuclear renography is also commonly used in the post-operative period for assessment obstruction alleviation. 10 We have previously reported that RPV can be assessed easily and accurately using automated 3D reconstruction. 8 This method has yet to be used to evaluate function in obstructed renal units that subsequently underwent surgical repair.…”
Section: Discussionmentioning
confidence: 99%